Analysis Of Msme Empowerment Model On Post-Flood Disaster Wetland Area In Hulu Sungai Tengah Regency - Setio Utomo; Noor Hidayati (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Abstract The purpose of this research activity was to create a model for empowering MSMEs in wetland areas after the flood disaster. The model that would be produced in this study was expected to be able to contribute in increasing the resilience of SMEs after the disaster in the Hulu Sungai Tengah Regency. The specific objectives of this study were a) Identifying the characteristics of MSME empowerment in the post-flood wetland area in Hulu Sungai Tengah Regency, b) Analyzing the pattern of MSME empowerment in the post-flood wetland area in Hulu Sungai Tengah Regency, c) Developing a MSME empowerment model in post-flood wetland area in Hulu Sungai Tengah Regency. The research used a quantitative method with a survey approach to MSMEs affected by the flood disaster in Hulu Sungai Tengah Regency using research instruments and supported by in-depth interviews to map the problems and policies that would be taken in empowering MSMEs affected by the disaster. Furthermore, a literature study was used to synchronize field conditions with all local government programs and related stakeholders to be assembled into a model for empowering MSMEs in post-disaster wetland areas in Hulu Sungai Tengah Regency. The data collection used field research and library research. The AHP method used Rapfish Software to formulate a structured decision model formulation with AHP modeling to set priorities for empowering MSMEs in post-flood disaster wetland areas in Hulu Sungai Tengah Regency. The results of research data analysis using Expert Choice 11 from expert respondents (Local Governments, MSMEs, Universities, and Companies), obtained the results of the criteria for marketing facilities (20%) and priorities/alternatives for MSME business resilience (38%) as strategies in empowerment program and increase the resilience of MSMEs post-flood disaster in wetland areas in Hulu Sungai Tengah Regency. Keywords: Empowerment, MSME, Post-flood Disaster